Einkommens- und Vermögensverteilung in Deutschland - Charlotte Bartels; Theresa Neef (Wirtschaftsdienst, 2024)
– This article outlines income and wealth distribution trends in Germany since the 19th century, compared to other Western industrialised countries. We first discuss the evolution of aggregate wealth-to-income ratios. We then explore how the concentration of income and wealth among the top percentile evolved since the 19th century. For the period after 1990, we analyse the entire distributions from top to bottom, exploring why Germany differs from France and the U.S. Among European countries, Germany exhibits one of the highest concentrations of income and wealth.
Keywords: D31; N30; E01; 330; Einkommensverteilung; Vermögensverteilung; Deutschland; Einkommensverteilung; Vermögensverteilung; Deutschland